STRATEGI COACHING CLASS DALAM MENINGKATKAN KREATIVITAS DAN INOVASI PRODUK OLAHAN SUMBER DAYA LOKAL UMKM ENTERPRENEUR MUDA KOTA MAGELANG - Nilasari, Ayunda Putri; Retnosari, Retnosari; Astutik, Erni Puji (Jurnal Pengabdian Bukit Pengharapan, 2024)
Vocational high school students and Untidar students are conditioned to have an independent spirit and are directed to be creative in teaching and learning activities, therefore it is expected that Vocational high school students and Untidar students can prepare themselves to face changes by maximizing cooking class training activities as an effort to be ready to face changes in the era of globalization and the digital era. With this activity, it is expected to help direct Vocational high school students and Untidar students as part of the millennial generation, in addition to increasing their insight to become a millennial generation that is in accordance with the ideals as the successors of the nation in the future to reduce unemployment, also helping them find the best solution for how to prepare themselves to become a millennial generation that can face increasingly competitive challenges in the era of globalization and the digital era to support the increase in the variety of processed and nutritional products based on local resources. In accordance with our expectations as one part of the educators and mentors of the younger generation; it feels like the tasks we have to do are not enough. There are still many tasks and responsibilities waiting in the future that are closely related to educating and creating the next generation of this nation who will be able to compete in the era of globalization and towards the creative, innovative and independent digital era 4.0 and 5.0.